Implementation of Civic Education In Empowering Islamic Communities Era of Revolution 5.0 - Mantik, Aliyah; Sodiq, Jafar (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The establishment of Smart Society 5.0 is very important because society will continuously be required to develop the ability to solve social problems that occur due to the emergence of the industrial revolution 4.0. In society 5.0, industry becomes a very important sector where technological developments, especially in the aspect of information and communication, require people to produce new innovations continuously.This is a reason that society 5.0 must have intelligence in order to realize ideal conditions. In the digital era, artificial intelligence (AI) as a form of technology in society 5.0 has the ability to replace human work with the aim of providing a high quality of life to society. It turns out that not only does it cause negative things to human work that is starting to be replaced by AI, the character of the nation and state also begins to be influenced by outside culture. The influence of speed in accessing information makes the opening of foreign culture enter and begin to affect the character of Indonesian society. As we know that many theories that explain Civic Education are viewed from various perspectives, both with regard to culture, economy, social, politics, and religion derived from the civilization of the nation's cultural values.Civic education is a very urgent need for the nation in building a prosperous, safe, comfortable, peaceful, prosperous life. Openness in the current 5.0 era, access to communication, and information can be misused and have a negative impact if not accompanied by a good character. Misuse of information media will have an impact on prolonged social issues. Then the empowerment of Islamic communities through religious moral values is expected to be a pillar in navigating the development of the times that require people to become quality human resources in order to welcome the era of revolution 5.0. This research uses a qualitative approach because researchers want to understand and reveal the problems that are being experienced by research subjects in depth. Qualitative research is research by collecting data in a natural setting with the intention of interpreting phenomena that are happening where researchers act as instruments.